Navigating the Decline: Strategies for Improving Gurame Fish Fry Production and Business Management in Tasikmalaya - Firman Syah ZA, Irvan; Taru Febriani Prajayati, Vini (Fakultas Pendidikan Ekonomi dan Bisnis, 2024)
Purpose—This study explored the current state and challenges of Gurame fish fry production in Tasikmalaya City despite its significant potential. The research aims to identify key issues affecting production levels and provide insights for potential improvements. Understanding these factors is crucial for addressing the decline in production and enhancing the industry's sustainability.Design/methods/approach – Data was collected through interviews with 25 randomly selected respondents from Gurame fish fry breeding groups. The research utilized qualitative methods to gather detailed information on production processes and problems faced by breeders.Findings – The study revealed that the decline in Gurame fish fry production is primarily attributed to weather conditions (52%) and disease outbreaks (17%). Additionally, the quality of broodstock also contributes to the reduction in fry production (8%). Currently, most breeders’ income ranges from Rp 500,000 to Rp 1,500,000, which is below the district's minimum wage.Research implications/limitations—This research's limitations include the small sample size and the reliance on self-reported data, which may affect the generalizability of the findings. The study also did not explore all potential factors affecting production, such as feed quality and management practices.Originality/value – This study provides valuable insights into the factors impacting Gurame fish fry production in Tasikmalaya City. It suggests that adopting recirculating aquaculture systems and improving broodstock quality by avoiding inbreeding could enhance production. Future research should explore these recommendations further and examine additional factors influencing production stability.